Pemberian Penguatan Terhadap Sosial Emosional Anak Usia Dini dalam Perspektif Islam Di Era Society 5.0 - Mushab, Mushab Al Umairi; Lillawati, Agustine (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2024)
This seminar was motivated by the inability of young children to properly control their social emotions from an Islamic perspective towards the environment, school, family and also society in the era of society 5.0. Early childhood is a time when the foundations are formed for the social and emotional development of a human being. So, a child's inability to control social and emotional emotions in accordance with the surrounding environment can cause the child to be isolated from his environment, not develop confidence in himself, and so on. As a result, children will experience obstacles in their further development. To help reduce a child's inability to control social and emotional well. So, help from adults is needed. In providing this assistance, parents or teachers should understand the process of social emotional development of early childhood. The formulation of this research problem discusses providing social and emotional strengthening to early childhood from an Islamic perspective in the era of society 5.0. The benefit of this seminar is that adults, both parents and teachers, pay attention to good social interactions in accordance with Islamic principles. The target for this seminar is PAUD institutions in Kel. Gununganyar Tengah, District. Gununganyar, City. Surabaya. The output of this community service is in the form of articles which will later be uploaded in mass media, journals with ISSN and IPR articles. The activity plan begins with planning including preparing materials, determining the location and administration. Then the implementation stage includes training activities. And the final part is reporting on community service activities.